Results of cellular immunity research in persons using fixed dentures based on different metal alloys. - Grizodub, D. V. (Medicni Perspektivi, 2014)
Purpose of the work was to explore the possibilities of forecasting adverse reactions based on the study of the immune system of the potential denture user and features of its interaction with potential materials of future depture. Methods:  The author conducted study of cellular immunity components in patients with complaints on intolerance of dentures. Results: The most pronounced negative dynamics of cellular immunity was observed in patients with cobalt-chromium alloys: marked reduction of T-lymphocytes, change in subpopulation ratio towards predominance of T-helper cells, which led to the development of cellular intolerance reactions, higher content of Ig E, increased histamine release in response to denture material. Comprehensive assessment of allergic history data, imune status parameters allows to carry out a preliminary assessment of materials biocompatibility and their individual selection in each case both in healthy subjects and in patients with allergic diseases. Identification of materials which have the ability to cause adverse reactions in particular patient caused by the action of histamine on the cells and tissues, allows to replace the material or not to use it in a particular patient.